Quality of sleep and musculoskeletal pain in adolescents: observational study - Batista,Jéssica Fernanda de Oliveira Lima (2022)
ABSTRACT BACKGROUND AND OBJECTIVES: Musculoskeletal pain (MSP) is related to psychogenic factors and quality of sleep, showing that this triad is a biopsychosocial process. The aim of this study was to analyze an association between poor sleep quality and MSP in adolescents. METHODS: This study has an observational, cross-sectional character, in which 545 adolescents, aged between 11 and 15 years, were analyzed. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), the presence of MSP using the Nordic Musculoskeletal Questionnaire (NMQ), temporomandibular disorder using the Axis II of the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) and excessive daytime sleepiness using the Epworth Sleepiness Scale (ESS). Pearson Chi-square or Fishers Exact test were used to assess the association between two categorical variables. RESULTS: The prevalence of poor sleep quality, sleep disorders, MSP and excessive daytime sleepiness were, respectively, 66.8, 9.5, 87.5 and 30.5%. An association was observed between the quality of sleep and the number of hours of sleep per night [OR = 1.49; (1.01 to 2.21)], and between sleep disorders and MSP in the upper back [OR=1.9; (1.0 to 3.3)], and the wrists and hands [OR=2.8; (1.4 to 5.7)]. However, there was no association between sleep quality and MSP [OR=1.29; (0.76 to 2.17)]. CONCLUSION: An association was found between sleep disorders and MSP, as well as between the number of hours slept per night and quality of sleep.